SUPERCONDUCTIVITY UP TO 105K IN THE NEW HIGH-TC TL-V-SR-CA-CU-O AND TL-V-SR-CA-Y-CU-O SYSTEMS - Liu, R; Zhou, W; Janes, R; Edwards, P (1990)
Superconductivity up to 105K has been observed in the TlVSrCaCuO and TlVSrCaYCuO systems using both electrical resistivity and magnetisation measurements. From the results of X-ray diffraction, energy dispersive spectrometry and selected area electron diffraction, we identify the phases responsible for the superconductivity to be (Tl0.72V0.28)Sr2CaCu2Oy (with Tc=80K) and (Tl0.72V0.28)Sr2(Ca0.86Y0.14)Cu2Oy (with Tc=105K). We propose that the partial substitution of vanadium for thallium in the crystal lattice stabilizes the TlSr2CaCu2Oy phase and enhances superconductivity up to 80K. Importantly, 20% of Y3+ replacement of Ca2+ sites in the (Tl, V)Sr2CaCu2Oy compound reduces the excess hole concentration and increases superconductivity by about 20K. © 1990.